Engineer's report - Douglas, Edwin A., 1805-1859 ([printer to the state], 1854)
November 13, 1854 Engineer's Report to the President and Board of Directors of the Cape Fear and Deep River Navigation Company. The report, authored by E.A. Douglas, reviewed the current state of the works and any suggested modifications for the improvement plan, as well as the cost of same. Financial statements of the estimated costs of completing both the present plan, and proposed plan, were included.